TEACHING WRITING A DESCRIPTIVE TEXT BY USING GUIDED WRITING STRATEGY - Lestari, Tian; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to investigate the effectiveness of teaching writing a descriptive text by using guided writing strategy at eighth grade students of SMP Negeri 17 Pontianak in Academic Year 2013/2014. Moreover, this research is intended to find out how effective teaching is teaching writing a descriptive text by using guided writing strategy at eighth grade students. The students’ problem in elements of identification makes hard for them to start their writing. They tend to jump to write the description of the subject without writing the identification. Meanwhile, identification is important in writing descriptive text. The second problem is the incorrect use of language features. They can not write correct sentence of simple present tense that is used in descriptive text. As the purpose of this research is to investigate the effectiveness of teaching writing descriptive text, the method used in this research is pre-experimental research with single group pre-test and post-test. One class of eighth grader of SMP Negeri 17 Pontianak were choses as the sample in this study. There were 34 students in the class. The findings of this research suggested that Guided Writing Strategy was highly effective in teaching writing a descriptive text as indicated by a statistically higher writing score of post-test (70,44) than pre-test (51,09). This difference was highly significant with the effect size value 1,36. Based on the research foundings, it can be conluded that the effectiveness of teaching writing a descriptive text by using guided writing is high. Thus, it is suggested for English teacher to use this strategy as an alternative for teaching writing. Kata kunci: descriptive text, guided writing strategy. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas mengajar menulis teks deskriptif dengan menggunakan strategi menulis terbimbing pada siswa kelas VIII SMP Negeri 17 Pontianak Tahun Ajaran 2013/2014 . Selain itu , penelitian ini bertujuan untuk mengetahui seberapa efektif mengajar menulis teks deskriptif dengan menggunakan strategi menulis terbimbing pada siswa kelas 8 . Masalah yang di hadapi siswa yaitu dalam menentukan identifikasi yang membuatnya sulit untuk mulai menulis. Mereka cenderung melompat untuk menulis teks deskripsi tanpa menulis identifikasi. Sementara itu, kalimat identifikasi sangat penting dalam menulis teks deskriptif. Masalah kedua adalah penggunaan yang salah dari fitur bahasa. Mereka tidak bisa menulis kalimat dalam bentuk simple present tense dengan benar yang digunakan dalam teks deskriptif. Sebagai tujuan dari penelitian ini adalah untuk mengetahui efektivitas mengajar menulis teks deskriptif, metode yang digunakan dalam penelitian ini adalah penelitian pre-eksperimental dengan satu kelompok pre - test dan post -test. Sampel penelitian adalah siswa-siswa Kelas 8. Ada 34 siswa di kelas. Temuan penelitian ini menunjukkan bahwa Strategi Menulis Dipandu sangat efektif dalam mengajar menulis teks deskriptif seperti yang ditunjukkan oleh skor menulis statistik lebih tinggi dari post-test ( 70,44 ) dari pre-test ( 51,09 ). Perbedaan ini sangat signifikan dengan efek nilai ukuran 1,36. Berdasarkan penelitian, dapat disimpulkan bahwa efektivitas mengajar menulis teks deskriptif dengan menggunakan dipandu menulis sangat tinggi. Oleh karena itu, disarankan bagi guru bahasa Inggris untuk menggunakan strategi ini sebagai alternatif untuk pengajaran menulis. Key words:teks deskriptif, strategi membimbing dalam menulis.